A Sugar Factory - (:unkn) unknown (The Bonanza, Smith Bros and Co., Trinidad, 2009)
Photo depicting a drawing of a sugar cane factory. There are horses, carts and workers outside the building of the factory.
Colour; Brown, Grey, Green; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Sugar trade; Sugar factories